Conductive sheet
The conductive sheet for fuel cell separators, featuring a layered structure with large and small conductive fillers and a graphite sheet, addresses the challenges of gas leakage and electrical conductivity, achieving effective gas-blocking and low resistance.
Patent Information
- Application Number
- JP2023147760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Conductive sheets used in fuel cell separators face challenges in achieving sufficient strength and gas-blocking properties while maintaining low electrical resistance, as they are prone to gas leakage due to cracking and increasing binder components to prevent cracking lowers electrical conductivity.
A conductive sheet with a specific layered structure, including a first surface conductive resin layer with large conductive fillers, an interposed conductive resin layer with small diameter conductive fillers, and a gas-blocking graphite sheet layer, which are integrally formed into a concave and convex shape to enhance adhesion and reduce physical damage during manufacturing.
The proposed conductive sheet achieves good gas-blocking properties and low resistance, effectively addressing the issues of gas leakage and electrical conductivity, while maintaining structural integrity.
Smart Images

Figure 2025040757000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrically conductive sheet, in particular to an electrically conductive sheet for use in a fuel cell separator. [Background technology]
[0002] Conventionally, fuel cell separators made of metal materials and those made of carbon materials have been developed. Fuel cell separators made of carbon materials are useful in terms of light weight, cost, chemical resistance, etc., compared to those mainly made of metal materials. However, such fuel cell separators sometimes do not have sufficient strength, and in particular, the probability of gas leakage due to cracks occurring is higher than that of metals. In addition, when the binder component such as resin is increased to prevent the cracks, the electrical conductivity decreases. Various proposals have been made to solve these problems.
[0003] Patent Document 1 discloses a fuel cell separator characterized by having a conductive gas barrier layer (B) on a conductive layer (A) in which conductive fibers are bound and solidified with a synthetic resin.
[0004] Patent Document 2 discloses a fuel cell separator comprising a substrate, the substrate including a first conductive layer comprising a first carbon material and formed in a resin material, and a second conductive layer comprising a second carbon material and formed adjacent to the first conductive layer on at least one side in the thickness direction of the first conductive layer and bonded to the first conductive layer via the resin material.
[0005] Patent document 3 discloses an electrically conductive article for use as an electrode in a fuel cell, which comprises electrically conductive reinforcement fibers contained in a matrix having a thickness with the fibers mechanically oriented to be parallel to the thickness.
[0006] Patent document 4 describes a method for manufacturing a fuel cell separator, which includes the steps of: producing a stampable sheet containing a conductive filler and a polymer material; supplying the stampable sheet to a molding machine equipped with a pair of dies engraved with the shape of a fuel cell separator; and thermoforming the stampable sheet supplied to the molding machine into the separator shape. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-15131 A [Patent Document 2] JP 2021-170524 A [Patent Document 3] Special Publication No. 2005-527092 [Patent Document 4] JP 2006-269313 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a novel conductive sheet having good gas barrier properties and low resistance. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that the above problems can be solved by the following means, and have completed the present invention. That is, the present invention is as follows: Aspect 1: A conductive sheet comprising: The insulating film has a first surface conductive resin layer, a first intervening conductive resin layer, and a gas barrier layer in this order, the first surface conductive resin layer contains a conductive large-diameter filler having a maximum diameter of 100 μm or more and a first binder resin; the first interposed conductive resin layer contains a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a second binder resin; The gas barrier layer is made of a graphite sheet, and Each layer constituting the conductive sheet is integrally formed into an uneven shape. Conductive sheet. <Aspect 2> The conductive sheet according to aspect 1, wherein each layer constituting the conductive sheet is formed in a wavy shape parallel to each other. <Aspect 3> The first surface conductive resin layer, the first intervening conductive resin layer, the gas barrier layer, the second intervening conductive resin layer, and the second surface conductive resin layer are provided in this order, the second surface conductive resin layer contains a conductive large-diameter filler having a maximum diameter of 100 μm or more and a first binder resin; The second interposed conductive resin layer contains a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a second binder resin. 3. The conductive sheet according to claim 1 or 2. <Aspect 4> The conductive sheet according to any one of aspects 1 to 3, wherein the first binder resin is in the form of a resin fiber aggregate. Aspect 5: The conductive sheet according to any one of aspects 1 to 4, wherein the second binder resin is at least one selected from the group consisting of polypropylene, polyethylene, polyamide, polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), liquid crystal polymer (LCP), polyimide (PI), polycarbonate (PC), polyphenylene ether (PPE), polysulfone (PSU), polyethersulfone (PES), polyetheretherketone (PEEK), polyurethane, epoxy resin, silicone resin, urea resin, phenolic resin, thermosetting polyimide, and thermosetting isocyanate. <Aspect 6> The conductive sheet according to any one of aspects 1 to 5, wherein the conductive large diameter filler is carbon fiber. Aspect 7: The conductive sheet according to any one of aspects 1 to 6, wherein the conductive small diameter filler is selected from the group consisting of carbon black, graphite, CNT, and graphene. Aspect 8: A fuel cell separator comprising the conductive sheet according to any one of aspects 1 to 7. Effect of the Invention
[0010] According to the present invention, a novel conductive sheet having good gas barrier properties and low resistance can be provided. [Brief description of the drawings]
[0011] [Figure 1] This figure is a cross-sectional side view of the conductive sheet of the present invention. [Diagram 2] This figure is a side cross-sectional view of a conventional conductive sheet. [Diagram 3] This figure is an explanatory diagram showing the method for producing a conductive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Conductive sheet As shown in FIG. 1, the conductive sheet 100 of the present invention is The insulating film has a first surface conductive resin layer 130, a first intervening conductive resin layer 120, and a gas barrier layer 110 in this order. the first surface conductive resin layer 130 contains a conductive large-diameter filler having a maximum diameter of 100 μm or more and a first binder resin; the first intervening conductive resin layer 120 contains a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a second binder resin; The gas barrier layer 110 is made of a graphite sheet, and The layers constituting the conductive sheet 100 are integrally formed into an uneven shape.
[0013] The above-mentioned uneven shape can be obtained by subjecting a laminate constituted by the above-mentioned layers to hot press molding.
[0014] In a fuel cell separator, an uneven shape may be provided for the purpose of ensuring a flow path for oxygen and / or hydrogen. As shown in Fig. 2, when an uneven shape is provided on the surface by simply locally pressing the surface conductive resin layer 220 without deforming the gas barrier layer 210, there is a drawback that the thickness of the fuel cell separator becomes large.
[0015] Moreover, when the fuel cell separator described in Patent Document 1 was simply formed into the uneven shape shown in FIG. 1, the graphite sheet sometimes broke.
[0016] The inventors have found that the above problem occurs because the large-diameter conductive filler contained in the surface conductive resin layer is pressed against the graphite sheet during press molding, and have discovered that the above problem can be solved by providing an intervening conductive resin layer between the surface conductive resin layer and the gas barrier layer.
[0017] Without wishing to be bound by theory, it is believed that this is because the interposed conductive resin layer acts as a protective layer during the manufacture of the conductive sheet, thereby suppressing physical damage caused by pressure welding or abrasion of the large-diameter conductive filler, and because the interposed conductive resin layer acts as a lubricating layer during hot pressing, thereby mitigating the stress that would be applied to the deformed areas.
[0018] In addition, the intervening conductive resin layer enhances the adhesion between the surface conductive resin layer and the gas barrier layer, thereby enabling a stable flow of electricity.
[0019] As shown in FIG. 1, the conductive sheet of the present invention may have a first surface conductive resin layer, a first intervening conductive resin layer, the gas barrier layer, a second intervening conductive resin layer, and a second surface conductive resin layer, in this order.
[0020] The layers constituting the conductive sheet may be formed in parallel wavy shapes.
[0021] The conductive sheet of the present invention is useful as a separator for a fuel cell. That is, the present invention also relates to a separator for a fuel cell that is constituted by the conductive sheet described above.
[0022] Each component of the present invention will now be described.
[0023] <First and second surface conductive resin layers> The first and second surface conductive resin layers contain a large-diameter conductive filler having a maximum diameter of 100 μm or more, and a first binder resin.
[0024] The manufacturing method of the first and second surface conductive resin layers can be appropriately adopted according to the form of the first binder resin. For example, when the first binder resin is a resin fiber aggregate, the first and second surface conductive resin layer precursors are prepared by a known papermaking method such as a wet papermaking method, and then the resin fibers of the first and second surface conductive resin layer precursors are melted by applying a heat press. In this case, the first and second surface conductive resin layer precursors contain a conductive large diameter filler having a maximum diameter of 100 μm or more and resin fibers before melting.
[0025] (Large diameter conductive filler) The conductive large diameter filler is a conductive filler having a maximum diameter of 100 μm or more. The lower limit of the maximum diameter may be, for example, 120 μm, 150 μm, 170 μm, 200 μm, 220 μm, 250 μm, 270 μm, or 300 μm. The upper limit of the maximum diameter is not particularly limited, but may be, for example, 2000 μm, 1800 μm, 1500 μm, 1200 μm, 1000 μm, 800 μm, or 500 μm.
[0026] The fact that the longest diameter of the conductive large diameter filler exceeds the above lower limit may be confirmed by confirming the presence of particles whose longest diameter exceeds the above lower limit using a scanning electron microscope (SEM) or the like, or may be confirmed by checking that the D50 of the conductive large diameter filler is equal to or greater than the above lower limit of the longest diameter.
[0027] In this specification, the method of measuring D50 is appropriately selected depending on the size of the particle to be measured. In the case of particles less than about 1 μm, D50 is the value of the histogram average particle diameter (D50) calculated on a volume basis in the scattering intensity distribution measured by the dynamic light scattering method, and in the case of particles of 1 μm or more, D50 is the value of the median diameter (D50) calculated on a volume basis in the laser diffraction method. The measurement of D50 can be performed using a particle size analyzer [Microtrac HRA9320-X100 (Nikkiso Co., Ltd.)].
[0028] As the conductive large diameter filler, for example, graphite particles, carbon fibers, carbonaceous large diameter fillers such as carbonaceous composite conductive filler particles, etc. Among them, it is preferable to use carbonaceous composite conductive fillers from the viewpoint of conductivity.
[0029] The content of the large diameter conductive filler in each surface conductive resin layer may be 30% by mass or more, 35% by mass or more, 40% by mass or more, or 45% by mass or more, and may be 80% by mass or less, 75% by mass or less, 70% by mass or less, 65% by mass or less, 60% by mass or less, or 55% by mass or less, relative to the mass of the surface conductive resin layer.
[0030] (Large diameter conductive filler: Carbonaceous composite conductive filler particles) The carbonaceous composite conductive filler particles include graphite particles and amorphous carbon coating the graphite particles.
[0031] In the above-mentioned carbonaceous composite conductive filler particles, the graphite particles are coated with amorphous carbon, which makes it possible to utilize the high conductivity of the graphite particles while suppressing problems caused by peeling at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves, making them suitable as conductive large-diameter fillers.
[0032] Here, the presence of amorphous carbon on the surface of the carbonaceous conductive filler particles can be confirmed by observing the G-band (1450 to 1700 cm) in the Raman spectroscopy of the conductive filler. -1 ) for D-band (1100~1450cm -1 ) is 0.5 or more, particularly 0.5 to 1.1. This ratio is less than 0.5 for graphite alone, and exceeds 1.1 for amorphous carbon alone. Therefore, the ratio of 0.5 to 1.1 is considered to be due to the fact that the amorphous carbon layer on the surface is thin or there are gaps in the amorphous carbon layer on the surface, which allows the spectrum due to the bonds derived from graphite to be obtained in addition to the spectrum due to the bonds derived from amorphous carbon.
[0033] The graphite particles contained in the carbonaceous composite conductive filler particles may be graphite particles in any form, such as flake-like, spherical, lump-like, or thin-flaky, but from the viewpoint of electrical conductivity, flake-like or spherical graphite particles are preferably used.
[0034] In the carbonaceous composite conductive filler particles, the ratio of graphite particles to the total of amorphous carbon and graphite particles may be 10% by mass to 95% by mass. A small ratio is preferable in order to cover the graphite particles with amorphous carbon and suppress problems such as peeling at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves. On the other hand, a large ratio is preferable in order to utilize the good conductivity of the graphite particles. This ratio may be 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, and may be 95% by mass or less, 90% by mass or less, 85% by mass or less, or 80% by mass or less.
[0035] Here, with regard to the present invention, "the ratio of graphite particles to the total of amorphous carbon and graphite particles" can be calculated based on the weight ratio of various raw materials in the manufacturing stage of the carbonaceous composite conductive filler particles and the sintered residual rate (carbon yield rate), with the residual rate of the graphite particles used being set at 100 mass%.
[0036] In the carbonaceous composite conductive filler particles, the graphite particles dispersed in the amorphous carbon may have a D50 of 1 μm to 100 μm. The graphite particles may have a D50 of 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 7 μm or more, 10 μm or more, 15 μm or more, 25 μm or more, or 20 μm or more, or may have a D50 of 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.
[0037] The carbonaceous composite conductive filler particles can be produced by any method. For example, graphite particles are dispersed in a resin material to obtain a graphite particle-containing resin block in which the graphite particles are dispersed in the resin material, the graphite particle-containing resin block is optionally cured and / or infusible, and then fired under an inert atmosphere to amorphously carbonize the resin material, thereby obtaining a graphite particle-containing amorphous carbon block, which is then pulverized and optionally classified to obtain the carbonaceous composite conductive filler particles. A known method can be used to disperse the graphite particles in the resin material.
[0038] The resin material to be carbonized amorphously used herein may be any thermoplastic resin or curable resin that is carbonized amorphously when fired in an inert atmosphere. Examples of the thermoplastic resin include, but are not limited to, thermoplastic polyimide resin (TPI), chlorinated polyvinyl chloride resin (CPVC), polyvinyl chloride resin (PVC), polyetherimide resin (PEI), or polyacrylonitrile resin (PAN). Examples of the thermosetting resin include, but are not limited to, polyimide resin, furan resin, or phenolic resin.
[0039] (First binder resin) The first binder resin may be a resin in any form, for example a resin fiber mass.
[0040] As the first binder resin, it is preferable to use a resin that has the characteristics of being resistant to the chemical environment of the fuel cell, not softening or melting at the reaction temperature of the fuel cell, and softening or melting during press molding. Examples of such resins that can be used include polypropylene, polyethylene, polyamide, polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), liquid crystal polymer (LCP), polyimide (PI), polycarbonate (PC), polyphenylene ether (PPE), polysulfone (PSU), polyethersulfone (PES), polyetheretherketone (PEEK), polyurethane, epoxy resin, silicone resin, urea resin, phenol resin, thermosetting polyimide, thermosetting isocyanate, and polymers or mixtures of two or more of the above.
[0041] (First binder resin: resin fiber aggregate) The resin fiber aggregate can be obtained by melting the resin fibers, particularly by partially melting them by heat pressing. The resin constituting the resin fibers may be any of the above-mentioned resins.
[0042] <First and second intervening conductive resin layers> The first and second intervening conductive resin layers contain a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a resin.
[0043] The thickness of the first and second intervening conductive resin layers may be 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, 10 μm or more, 12 μm or more, 15 μm or more, 17 μm or more, 20 μm or more, or 22 μm or more, and may be 300 μm or less, 250 μm or less, 220 μm or less, 200 μm or less, 180 μm or less, 150 μm or less, 120 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.
[0044] The interposed conductive resin layer may be manufactured by mixing and dispersing the conductive small diameter filler in the second binder resin to obtain a resin composition, forming this into a film by a known film-forming method, such as a melt casting method or an inflation method, and placing this on the gas barrier layer.
[0045] In another embodiment, the intervening conductive resin layer may be produced by adding the conductive small diameter filler and the second binder resin to a solvent to prepare an ink, and then disposing this on the gas barrier layer.
[0046] (Small diameter conductive filler) The conductive small diameter filler is a conductive filler having a D50 of 50 μm or less as measured by a laser diffraction method. This D50 may be 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, or 12 μm or less, and may be 10 nm or more, 30 nm or more, 50 nm or more, 70 nm or more, 100 nm or more, 120 nm or more, 150 nm or more, or 170 nm or more.
[0047] The conductive small diameter filler may be, for example, a carbonaceous small diameter filler, an inorganic conductive small diameter filler, etc. These may be used alone or in combination.
[0048] Examples of the carbonaceous small diameter filler that can be used include carbon black, graphite, CNT, and graphene.
[0049] Examples of inorganic conductive small diameter fillers that can be used include particles of simple metals such as silver and copper, ceramics, metal compounds such as ITO, ATO, and tin oxide, and optional particles or fibers coated with these.
[0050] The content of the conductive small diameter filler in each intervening conductive resin layer may be 50 mass% or more, 55 mass% or more, 60 mass% or more, or 65 mass% or more, and may be 80 mass% or less, 75 mass% or less, or 70 mass% or less, relative to the mass of the intervening conductive resin layer.
[0051] (Second binder resin) As the second binder resin, it is preferable to use a resin that has the characteristics of being resistant to the chemical environment of the fuel cell, not softening or melting at the reaction temperature of the fuel cell, and softening or melting during press molding. Examples of such resins that can be used include polypropylene, polyethylene, polyamide, polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), liquid crystal polymer (LCP), polyimide (PI), polycarbonate (PC), polyphenylene ether (PPE), polysulfone (PSU), polyethersulfone (PES), polyetheretherketone (PEEK), polyurethane, epoxy resin, silicone resin, urea resin, phenol resin, thermosetting polyimide, thermosetting isocyanate, and polymers or mixtures of two or more of the above.
[0052] <Gas barrier layer> The gas barrier layer is composed of a graphite sheet.
[0053] (Graphite sheet) As the graphite sheet, for example, an expanded graphite sheet can be used.
[0054] The thickness of the graphite sheet may be 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, or 95 μm or more, and may be 300 μm or less, 270 μm or less, 250 μm or less, 220 μm or less, 200 μm or less, 170 μm or less, 150 μm or less, 130 μm or less, 120 μm or less, 115 μm or less, 110 μm or less, or 105 μm or less.
[0055] <<Method of manufacturing conductive sheet>> The method of the present invention for producing a conductive sheet, as shown in FIG. Providing a gas barrier layer 110 made of a graphite sheet (FIG. 3(a)); Providing an intervening conductive resin layer 120, 120' on the gas barrier layer 110 (FIG. 3(b)); Laminating the precursors 130a, 130'a for the surface conductive resin layer on the gas barrier layer 110 via the intervening conductive resin layers 120, 120' (FIG. 3(c)); and The layers are integrated into an uneven shape, and the resulting laminate is heat-pressed to melt the resins of the first and second surface conductive resin layer precursors. For example, when the first binder resin is composed of a resin fiber aggregate, the resin fibers of the first and second surface conductive resin layer precursors are melted to obtain a conductive sheet (FIG. 3(d)). Includes. EXAMPLES
[0056] The present invention will be specifically described with reference to examples and comparative examples, but the present invention is not limited to these.
[0057] <<Preparation of conductive sheet>> Example 1 50 parts by mass of nylon fiber, 20 parts by mass of carbon fiber (length longer than 1 mm), and 30 parts by mass of conductive granular filler with a D50 of 200 μm were dispersed in water, and a sheet with a basis weight of 100 g / m was produced by a wet papermaking method. 2 A precursor for a surface conductive resin layer was prepared.
[0058] Next, a liquid composition for the first and second intervening conductive resin layers was prepared by melt-mixing a total of 68.13 parts by mass of carbon black (D50=200 nm), graphite (D50=10 μm), and CNT (outer diameter 9.5 nm, length 5 μm or less) as conductive small diameter fillers, and 31.87 parts by mass of PVDF resin as resin, in NMP solvent. This was applied to both sides of a 100 μm thick graphite sheet as a gas barrier layer so that the film thickness after drying was 25 μm, and then dried to obtain the first and second intervening conductive resin layers.
[0059] The above-mentioned surface conductive resin layer precursors were placed on both sides of the obtained sheet, respectively, to obtain a laminate having a first surface conductive resin layer precursor, a first intervening conductive resin layer, a gas barrier layer, a second intervening conductive resin layer, and a second surface conductive resin layer precursor in this order. The laminate was molded into a waveform shape shown in FIG. 1 by heat pressing, thereby changing the first and second surface conductive resin layer precursors into the first and second surface conductive resin layers, respectively, to obtain a conductive sheet of Example 1. The molding was performed by pressing the laminate at a temperature of 250° C. and a pressure of 10 MPa, then cooling it to 70° C. under pressure, and removing the pressed laminate.
[0060] Example 2 and Comparative Examples 1 and 2 Conductive sheets of Example 2 and Comparative Examples 1 and 2 were produced in the same manner as in Example 1, except that the thicknesses of the gas barrier layer and the interposed conductive resin layer were changed as shown in Table 1.
[0061] "evaluation" <Gas permeability> The gas permeability of the conductive sheet was measured by the differential pressure method according to JIS K7126-1: 2006. Helium was used as the test gas, and the pressure of the high-pressure side test gas was set to 100 kPa.
[0062] <resistance> Carbon paper was placed on both sides of the conductive sheet, which was then sandwiched between gold-plated flat electrodes and a pressure of 1 MPa was applied. A current of 1 A was then applied to the flat electrodes, and the resistance at the interface between the flat electrodes and the carbon paper was subtracted from the resistance obtained by measuring the voltage between the electrodes to measure the resistance at the interface between the conductive sheet and the carbon paper.
[0063] The configurations and evaluation results of the examples and comparative examples are shown in Table 1. Note that "Not measurable" for gas permeability in Table 1 indicates that the amount of gas permeation over time could not be measured due to breakage of the conductive sheet.
[0064] [Table 1]
[0065] From Table 1, it can be seen that the conductive sheets of the examples having a surface conductive resin layer containing conductive small-diameter filler with a D50 of 50 μm or less and a second binder resin have good gas barrier properties and low resistance. [Explanation of symbols]
[0066] 100 Conductive sheet 110 Gas barrier layer 120, 120' intervening conductive resin layer 130, 130' surface conductive resin layer 130a, 130a' Surface conductive resin layer precursor 200 Conventional conductive sheet 210 Gas barrier layer 220, 220' surface conductive resin layer
Claims
1. A conductive sheet comprising: The insulating film has a first surface conductive resin layer, a first intervening conductive resin layer, and a gas barrier layer in this order, the first surface conductive resin layer contains a conductive large-diameter filler having a maximum diameter of 100 μm or more and a first binder resin; the first interposed conductive resin layer contains a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a second binder resin; The gas barrier layer is made of a graphite sheet, and Each layer constituting the conductive sheet is integrally formed into an uneven shape. Conductive sheet.
2. The conductive sheet according to claim 1 , wherein each layer constituting the conductive sheet is formed in a wavy shape parallel to each other.
3. the first surface conductive resin layer, the first intervening conductive resin layer, the gas barrier layer, the second intervening conductive resin layer, and the second surface conductive resin layer are arranged in this order; the second surface conductive resin layer contains a conductive large-diameter filler having a maximum diameter of 100 μm or more and a first binder resin; the second interposed conductive resin layer contains a conductive small diameter filler having a D50 of 50 μm or less as measured by a laser diffraction method, and a second binder resin; The conductive sheet according to claim 1 or 2.
4. The conductive sheet according to claim 1 , wherein the first binder resin is in the form of a resin fiber aggregate.
5. 3. The conductive sheet according to claim 1 or 2, wherein the second binder resin is at least one selected from the group consisting of polypropylene, polyethylene, polyamide, polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), liquid crystal polymer (LCP), polyimide (PI), polycarbonate (PC), polyphenylene ether (PPE), polysulfone (PSU), polyethersulfone (PES), polyetheretherketone (PEEK), polyurethane, epoxy resin, silicone resin, urea resin, phenolic resin, thermosetting polyimide, and thermosetting isocyanate.
6. The conductive sheet according to claim 1 or 2, wherein the conductive large diameter filler is carbon fiber.
7. 3. The conductive sheet according to claim 1, wherein the conductive small diameter filler is selected from the group consisting of carbon black, graphite, CNT, and graphene.
8. A fuel cell separator comprising the conductive sheet according to claim 1 or 2.
Citation Information
Patent Citations
Separator for fuel cell, its manufacture, and fuel cell
JP2001015131A
Carbon fiber reinforced plastic bipolar plate with continuous electrical path
JP2005527092A
Manufacturing method of separator for fuel cell
JP2006269313A
Separator for fuel cell and method for manufacturing separator for fuel cell
JP2021170524A